2022
DOI: 10.3389/fnut.2022.1039697
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel human intestinal Enterococcus faecium FUA027 capable of producing urolithin A from ellagic acid

Abstract: Urolithin A (UA) has received considerable research attention because of its health benefits. However, only a few strains have been reported to produce UA from ellagic acid (EA), and the molecular mechanisms underlying the gut microbiota-mediated transformation of ellagic acid into urolithin A is limited. In the present study, a single strain FUA027 capable of converting ellagic acid into UA in vitro was isolated from the fecal samples. The strain was identified as Enterococcus faecium through the morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…However, we cannot conclude that they are solely responsible for this activity. Rare, strain-specific urolithin A production has been reported for Bifidobacterium pseudocatenulatum INIA P815 36 , Streptococcus thermophilus FUA329 58 , and Enterococcus faecium FUA027 58 , which may be a result of horizontal gene transfer since it is not shared by other members of the taxa. Thus, further enzyme discovery efforts are necessary to understand urolithin production in these bacteria.…”
Section: Discussionmentioning
confidence: 98%
“…However, we cannot conclude that they are solely responsible for this activity. Rare, strain-specific urolithin A production has been reported for Bifidobacterium pseudocatenulatum INIA P815 36 , Streptococcus thermophilus FUA329 58 , and Enterococcus faecium FUA027 58 , which may be a result of horizontal gene transfer since it is not shared by other members of the taxa. Thus, further enzyme discovery efforts are necessary to understand urolithin production in these bacteria.…”
Section: Discussionmentioning
confidence: 98%
“…Very few studies have reported strains involved in the metabolism of ellagic acid to urolithin A, including Bifidobacterium pseudocatenulatum INIA P815, Lactococcus garvieae FUA009, Enterococcus faecium FUA027 and Streptococcus thermophilus FUA329. 40,43,46,47 Among three metabotypes, UM0 showed the lowest diversity and richness of intestinal bacteria, while UMB had the highest richness at phylum and family level. 144 The higher richness of gut microbiome may explain why UMB produces more types of metabolites than UMA.…”
Section: Reviewmentioning
confidence: 99%
“…Enterococcus faecium FUA027 within the human intestine can produce UA, and this strain was successfully isolated. [ 180 ] If the metabolite‐producing microorganisms are found, they can be developed into probiotics. Furthermore, when completely understanding the process by which microorganisms produce metabolites, analogs of the intermediates and drugs targeting crucial enzymes in microbial metabolism can be designed.…”
Section: Novel Strategies Explored For Cancer Treatment Based On the ...mentioning
confidence: 99%